THU0657 Effects of adalimumab initiation on corticosteroid utilisation and medical costs among patients with rheumatoid arthritis. (12th June 2018) - Qiao, Y.; Winthrop, K.L.; Griffith, J.; Kaplan, C.M.; Spivey, C.A.; Postlethwaite, A.; Wang, J.
Abstract : Background: Treatment guidelines recommend low dose corticosteroids (steroids) as a short-term (<3 months) therapy among rheumatoid arthritis (RA) patients to 'bridge' patients until benefits of disease modifying anti-rheumatic drugs (DMARDs) are observed. 1 However, for many patients it may be difficult to wean/eliminate steroids once they are initiated. Initiation of more effective therapies such as biologics may help promote reduction in steroid use. Objectives: This study examined the impact of initiating adalimumab (ADA) on steroid utilisation and medical costs among patients with RA. Methods: A retrospective analysis was conducted among adult RA patients initiating ADA as the initial biologic in the MarketScan Database (2012–2016). Study outcomes included whether oral/injectable steroids were used, daily dose, dosage categories (<5 and≥5 mg/day), number of steroid injections, and medical costs. Outcomes were compared 6 months pre- and post ADA initiation using Chi-square tests for categorical variables and paired t-tests and Wilcoxon rank sum tests for continuous variables. Because various types of variables were used for study outcomes, mixed effects logistic, classical linear, multinomial logistic models, and linear model with a log link and gamma distribution were used to adjust for patient demographic and health characteristics such as age, gender, health plan type, census region, and Charlson Comorbidity Index. Results: The study sample included 6, 214 ADA initiators. As compared to the 6 months prior to ADA initiation, there was a reduction in proportions of patients using oral steroids (from 72% to 59.5%) and injectable steroids (from 34.9% to 26.9%), average daily dose of oral steroids (from 3.3 mg/day to 2.5 mg/day), patients with dose ≥5 mg/day (from 22.3% to 15.1%), number of steroid injections (from 0.63 to 0.47), and medical costs (from 5, 233.5 to 4, 807.9) (p<0.01 for all comparisons). Multivariate analysis produced similar patterns. In the 6 months post-ADA initiation, patients were less likely to use oral steroids (Odds Ratio (OR): 0.40; 95% Confidence Interval (CI): 0.36–0.45) or steroid injections (OR: 0.59; 95% CI: 0.54–0.65). Coefficient estimate for daily dose reduction was −0.87 (95% CI: −1.00- −0.74). Post-ADA relative risk ratios for dosage categories<5 mg/day and ≥5 mg/day compared to zero were 0.48 (95% CI: 0.43–0.53) and 0.36 (95% CI: 0.32–0.41), respectively. Post-ADA incidence rate ratio for number of steroid injections was 0.72 (95% CI: 0.69–0.76). Ratio estimate for medical costs was 0.84 (95% CI: 0.79–0.89). All multivariate results reported were significant (p<0.01). Conclusions: Among patients with RA, following ADA initiation, there is a reduction in steroid utilisation and its dose, and patients' medical costs. Prospective studies should be conducted to confirm this relationship in the future. Reference: [1] Singh JA, et al. doi:10.1002/acr.22783 Acknowledgements: Financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: Y. Qiao Grant/research support from: AbbVie, K. Winthrop Grant/research support from: AbbVie, Consultant for: AbbVie, J. Griffith Shareholder of: AbbVie, Employee of: AbbVie, C. Kaplan Grant/research support from: AbbVie, C. Spivey Grant/research support from: AbbVie, A. Postlethwaite Grant/research support from: AbbVie, J. Wang Grant/research support from: AbbVie